Lithium supplementing material, positive electrode sheet, secondary battery, and electronic device

CN117059807BActive Publication Date: 2026-09-04BYD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210500356.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-07
Publication Date
2026-09-04
Estimated Expiration
2042-05-07

AI Technical Summary

Technical Problem

[0003]在锂二次电池首次充电过程中,负极表面形成固态电解质膜(SEI)会消耗大量的活性锂,导致电池的首次库伦效率和电池容量降低,故需要对锂二次电池进行补锂

Benefits of technology

[0109]为突出本申请的有益效果,设置以下对比例。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117059807B_ABST
    Figure CN117059807B_ABST
Patent Text Reader

Abstract

The application provides a lithium supplementing material, a positive electrode sheet, a secondary battery and an electronic device, the lithium supplementing material comprising a compound of a chemical formula of Li2(C2O4) x (SO3) y wherein x+y=1. The lithium supplementing material has a low delithiation potential, can delithiate active lithium at a low potential, thereby supplementing the active lithium consumed during the first charging, avoiding the damage of high-voltage charging to the structure of the electrode material, and improving the capacity and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, specifically to a lithium replenishment material, a positive electrode sheet, a secondary battery, and an electronic device. Background Technology

[0002] Lithium-ion batteries have been widely used in end products (smartphones, digital cameras, laptops, and electric vehicles) due to their advantages such as high energy density, high operating voltage, long service life, low self-discharge rate, and environmental friendliness.

[0003] During the initial charging of a lithium-ion battery, the formation of a solid electrolyte interphase (SEI) film on the negative electrode surface consumes a significant amount of active lithium, leading to a decrease in the battery's initial coulombic efficiency and capacity. Therefore, lithium replenishment is necessary. However, existing lithium replenishment materials have high delithiation potentials, making them only suitable for high-voltage lithium-ion battery systems. For ordinary lithium-ion batteries, high charging voltages cause irreversible structural changes in the electrode materials, thereby reducing their structural stability and the battery's cycle performance. Therefore, it is essential to develop a lithium replenishment material with a lower delithiation potential to avoid damage to the electrode materials from high voltage and extend the battery's lifespan. Summary of the Invention

[0004] In view of this, this application provides a lithium replenishment material with a low delithiation potential, which can remove active lithium at a low potential, thereby replenishing the active lithium consumed during the first charge, avoiding damage to the electrode material structure caused by high-voltage charging, and improving the battery capacity and cycle performance.

[0005] The first aspect of this application provides a lithium supplement material, comprising the chemical formula Li2(C2O4). x (SO3) y A compound in which x + y = 1.

[0006] This application demonstrates that doping lithium oxalate with a certain amount of sulfite can expand the interlayer spacing of lithium oxalate crystals, making the crystal structure of lithium oxalate looser, reducing intermolecular forces, thus reducing the polarization voltage required for the decomposition of the lithium replenishment material, thereby reducing the delithiation potential of the lithium replenishment material and achieving lithium replenishment at low charging voltage.

[0007] Optionally, the ratio of x to y is greater than or equal to 9.

[0008] Optionally, the value of x is greater than or equal to 0.9 and less than 1.

[0009] Optionally, the particle size of the lithium replenishing material is 1 nm to 20 μm.

[0010] Optionally, the particle size of the lithium replenishing material is 0.1 μm to 5 μm.

[0011] Optionally, the decomposition potential of the lithium replenishment material is less than or equal to 4.6V.

[0012] Secondly, this application provides a positive electrode sheet, which includes an active material and a lithium supplementation material as described in the first aspect of this application.

[0013] Optionally, the positive electrode includes a current collector and an active material layer disposed on the current collector, the active material layer including the active material and the lithium supplementation material.

[0014] Optionally, the positive electrode includes a current collector, a positive electrode material layer, and a lithium replenishment layer arranged sequentially, wherein the positive electrode material layer includes the active material, and the lithium replenishment layer includes the lithium replenishment material.

[0015] Optionally, the mass ratio of the lithium replenishing material to the active material is 1:(5-1000).

[0016] Optionally, the mass ratio of the lithium replenishing material to the active material is 1:(10-100).

[0017] Optionally, the active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxide phosphate, lithium vanadium oxide, and lithium-rich manganese-based materials.

[0018] Optionally, the active material has a mass percentage content of 80%-99.9% in the active material layer.

[0019] Optionally, the lithium replenishing material has a mass percentage content of 0.1%-15% in the active material layer.

[0020] Optionally, the active material layer further includes a conductive agent and a binder.

[0021] Optionally, the adhesive includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile, and polyacrylate.

[0022] Optionally, the conductive agent includes one or more of acetylene black, carbon black, carbon nanotubes, carbon nanofibers, activated carbon, and graphene.

[0023] Thirdly, this application provides a secondary battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode includes a positive electrode sheet as described in the second aspect of this application.

[0024] Fourthly, this application provides an electronic device comprising a positive electrode as described in the third aspect of this application. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the structure of a secondary battery provided in an embodiment of this application;

[0026] Figure 2 The charge-discharge curves of the test batteries in Examples 1-3 are shown.

[0027] Figure 3 The charge-discharge curves of the test batteries in Examples 4-6 are shown.

[0028] Figure 4 The charge-discharge curves of the test batteries for comparative examples 1-2 are shown. Detailed Implementation

[0029] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0030] Existing lithium supplementation materials, such as lithium oxalate (Li₂C₂O₄), have a decomposition and delithiation voltage as high as 4.7V, making them only suitable for high-voltage lithium-ion battery systems, such as high-voltage cathode materials like LiNi. 0.5 Mn 1.5 The operating voltage of O2 (lithium nickel manganese oxide) is 4.7-4.8V. However, for most cathode materials, the decomposition and delithiation voltage of the lithium replenishment material at 4.7V is much higher than the charging cutoff voltage of the cathode material. Higher charging voltages result in greater irreversible changes in the cathode material structure, leading to reduced structural stability and poorer battery cycle performance. Conversely, charging at lower potentials prevents sufficient delithiation, resulting in poor replenishment and lower coulombic efficiency during the first charge, which is detrimental to battery capacity. Therefore, this application provides a lithium replenishment material with a low decomposition potential, suitable for most current cathode materials, facilitating effective lithium replenishment and improving battery capacity and cycle performance.

[0031] The lithium supplementation materials provided in this application include those with the chemical formula Li2(C2O4). x (SO3) y The compound, where x + y = 1, x > 0 and y > 0, means that the anionic composition satisfies the principle of electroneutrality. In this lithium-supplementing material, Li2(C2O4) x (SO3) y The anion C2O4 2- and SO3 2- Both have a valence state of -2, and C2O42- and SO3 2- Since their relative molecular masses are similar, SO3 2- The doping of Li2(C2O4) has little effect on the lithium replenishment capacity. x (SO3) y It has a similar lithium replenishment capacity to lithium oxalate; doped with SO3 ions. 2- Sulfur atoms containing lone pairs of electrons and C2O4 2- The carbon atoms polarized by oxygen atoms have electrostatic forces, and the sulfur atoms have electrostatic repulsion with the negatively charged oxygen atoms. This makes the doped SO3 ions... 2- Interlayer insertion of SO3 in Li2C2O4 with a conical structure 2- Having a large radial length increases the interlayer spacing of Li2C2O4, making its crystal structure looser and weakening the intermolecular forces, hence Li2(C2O4) x (SO3) y The polarization voltage required for decomposition is reduced, resulting in a lower decomposition potential; in addition, SO3 2- Doping can also improve the conductivity of lithium-filling materials and promote their decomposition.

[0032] In some embodiments of this application, the value of x is greater than or equal to 0.9 and less than 1, and correspondingly, the value of y is less than or equal to 0.1, that is, the ratio of x to y is greater than or equal to 9. The specific values ​​of x can be, but are not limited to, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or 0.999. The specific values ​​of y can be, but are not limited to, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, or 0.001. The specific ratio of x to y can be, but is not limited to, 9, 9.5, 10, 10.5, 11, 13, 15, 18, 20, 22, 25, 30, 35, or 40. Controlling the value of x or y is equivalent to controlling SO3. 2- The doping amount when SO3 2- When the doping amount is 0, the material is lithium oxalate. Lithium oxalate has a theoretical specific capacity of 526 mAh / g, but it has a high decomposition and lithium-ion potential, resulting in poor compatibility with the charging cutoff voltage of conventional batteries. This application research found that doping lithium oxalate with a small amount of SO3... 2- This can lower the decomposition potential of lithium oxalate, as SO3 2- As the content increases, the decomposition potential of the material continuously decreases. When the value of x is greater than or equal to 0.9 and less than 1, the dopant ion SO3... 2-The increased interlayer spacing of lithium oxalate lattice is sufficient to ensure that the lithium replenishment material has a low decomposition potential. The initial charging at this low potential has virtually no impact on the positive electrode active material, electrolyte, and other battery components, thus ensuring good battery stability. Furthermore, when y is less than or equal to 0.1, SO3... 2- The low content of lithium can reduce the impact of dopant ions on the cathode material and ensure that the cathode material can be inserted and extracted in an orderly manner.

[0033] In this application, the lithium replenishment material decomposes at its decomposition potential to generate active lithium, thereby achieving lithium replenishment. Specifically, during the first charge of the secondary battery, Li2(C2O4)... x (SO3) y Within the set charge / discharge range, it will undergo self-decomposition, and the decomposition product is active lithium (Li). + And carbon dioxide gas (CO2) and a small amount of SO4 2- Active lithium (Li) + It can replenish the active lithium consumed by the formation of the solid electrolyte membrane (SEI) on the negative electrode surface, thereby increasing the battery capacity. The gas generated during the decomposition process can be safely discharged during the first charge and has no impact on the battery performance.

[0034] In this embodiment, the decomposition potential of the lithium replenishment material is less than or equal to 4.6V. This decomposition potential is well compatible with the charging cutoff voltage of conventional batteries and will not affect the positive electrode active material, electrolyte, or other battery components. Simultaneously, it ensures that the lithium replenishment material can fully decompose and release active lithium to compensate for the active lithium consumed in the formation of the solid electrolyte membrane (SEI) at the negative electrode, resulting in a good lithium replenishment effect. In some embodiments of this application, the decomposition potential of the lithium replenishment material is greater than or equal to 4.4V and less than or equal to 4.6V. This decomposition potential is applicable to most positive electrode materials, such as lithium iron phosphate (charging cutoff voltage 3.8V) and lithium nickel cobalt manganese oxide (NCM, charging cutoff voltage 4.35V). Using this lithium replenishment material can avoid irreversible structural changes in the positive electrode material under prolonged high charging voltage conditions while ensuring sufficient lithium replenishment, thereby improving the battery's stability and cycle performance.

[0035] In some embodiments of this application, the particle size of the lithium replenishment material is 1 nm to 20 μm. Specifically, but not limited to, the particle size of the lithium replenishment material can be 1 nm, 10 nm, 50 nm, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, or 5 μm. In some embodiments, the particle size of the lithium replenishment material is 0.1 μm to 5 μm. In some embodiments, the particle size of the lithium replenishment material is 0.3 μm to 1 μm. Controlling the particle size of the lithium replenishment material facilitates sufficient contact between the lithium replenishment material and the positive electrode material, thereby achieving uniform lithium replenishment. Furthermore, the lithium replenishment material can also fully contact the conductive agent, thereby accelerating the decomposition rate of the lithium replenishment material and ensuring that it decomposes at a lower potential. This allows the lithium replenishment material to fully decompose before the charging cutoff voltage, fully releasing active lithium to maximize lithium replenishment. In addition, the lithium replenishment material with this particle size distribution is easy to prepare, has good particle dispersion, and exhibits good stability in air, is not easily absorbing water and deteriorating, thus achieving effective lithium replenishment of the battery.

[0036] The lithium replenishment material provided in this application has a low decomposition potential and a high lithium replenishment capacity. (Li2(C2O4)) x (SO3) y doped SO3 2- The introduction of this material increases the interlayer spacing and loosens the crystal structure of lithium oxalate, weakening intermolecular forces and reducing the polarization voltage required for decomposition, thus lowering the decomposition potential. Adding this material to a battery enables decomposition and lithium release under low-voltage conditions, achieving lithium replenishment and preventing irreversible structural changes in the cathode material under sustained high charging voltages, thereby improving battery stability and cycle performance. Furthermore, the decomposition voltage of this material can be adjusted by changing the content of dopant groups and the particle size, allowing it to match the highest charging cutoff voltage that the battery system can withstand, thereby achieving a larger lithium replenishment capacity without affecting the battery system.

[0037] The lithium-supplementing material of this application can be prepared by different methods, and the specific preparation method is not limited. In some embodiments, the preparation method of the lithium-supplementing material includes: dissolving oxalic acid and sulfurous acid in water, adding lithium hydroxide to the solution to obtain a mixed solution of lithium oxalate and lithium sulfite, and evaporating and crystallizing the mixed solution at 40°C to 100°C to obtain Li2(C2O4). x (SO3) y ·zH2O, then add Li2(C2O4) x (SO3) y Li2(C2O4) was obtained by vacuum drying of zH2O at 100℃~200℃. x (SO3) yIn some embodiments, the method for preparing the lithium supplement material includes: dissolving lithium oxalate and lithium sulfite in water to obtain a mixed solution, and evaporating and crystallizing the mixed solution at 40°C to 100°C to obtain Li2(C2O4). x (SO3) y ·zH2O, then add Li2(C2O4) x (SO3) y Li2(C2O4) was obtained by vacuum drying of zH2O at 100℃~200℃. x (SO3) y .

[0038] The lithium supplementation material provided in this application has a simple preparation method, readily available raw materials, low production cost, and can be easily mass-produced, making it widely applicable to industrial production.

[0039] This application also provides a positive electrode sheet, which includes an active material and the lithium supplementation material of this application.

[0040] In some embodiments of this application, the active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxide phosphate, lithium vanadium oxide, and lithium-rich manganese-based materials. The lithium replenishment material of this application has a low decomposition potential, enabling lithium replenishment to be achieved at lower voltage ranges. Therefore, it is compatible with most cathode materials, suppresses structural changes in cathode materials under high voltage, and extends the cycle performance of the battery.

[0041] In some embodiments of this application, the mass ratio of the lithium replenishing material to the active material is 1:(5-1000), meaning the amount of lithium replenishing material added relative to the active material is 0.1%-20%. The specific mass ratio of the lithium replenishing material to the active material can be, but is not limited to, 1:5, 1:10, 1:15, 1:20, 1:50, 1:80, 1:100, 1:200, 1:400, 1:600, 1:800, or 1:1000. In some embodiments of this application, the mass ratio of the lithium replenishing material to the active material is 1:(10-100), meaning the amount of lithium replenishing material added relative to the active material is 1%-10%. In some embodiments of this application, the mass ratio of the lithium replenishing material to the active material is 1:(20-50), meaning the amount of lithium replenishing material added relative to the active material is 2%-5%. Controlling the amount of lithium replenishing material added ensures sufficient lithium replenishment to the battery, improves the battery's initial efficiency, and helps control the formation process time, reducing the occurrence of side reactions.

[0042] In some embodiments of this application, the positive electrode includes a current collector and an active material layer disposed on the current collector. The active material layer includes an active material and a lithium-supplementing material. In some embodiments of this application, the active material layer further includes a conductive agent and a binder. The conductive agent may be one or more of acetylene black, carbon black, carbon nanotubes, carbon nanofibers, activated carbon, and graphene. The binder may be one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile, and polyacrylate.

[0043] In some embodiments of this application, the mass percentage of the active material in the active material layer is 80%-99.9%. Specifically, the mass percentage of the active material in the active material layer may be, but is not limited to, 80%, 85%, 89%, 90%, 93%, 95%, 98%, or 99.9%. In some embodiments of this application, the mass percentage of the lithium-supplementing material in the active material layer is 0.1%-15%. Specifically, the mass percentage of the lithium-supplementing material in the active material layer may be, but is not limited to, 0.1%, 1%, 3%, 5%, 10%, or 15%. In some embodiments of this application, the mass percentage of the binder in the active material layer is 0.1%-15%. In some embodiments of this application, the mass percentage of the conductive agent in the active material layer is 0.1%-20%.

[0044] This application also provides a method for preparing the above-mentioned positive electrode sheet. In some embodiments, the method for preparing the positive electrode sheet includes a direct mixing method, which includes: mixing lithium supplementation material, positive electrode material, conductive agent, binder and solvent to form a positive electrode slurry, coating the positive electrode slurry on the surface of the current collector and drying it to obtain the positive electrode sheet.

[0045] In some embodiments of this application, the positive electrode sheet includes a current collector, a positive electrode material layer, and a lithium replenishment layer sequentially disposed therefrom. The positive electrode material layer includes an active material, and the lithium replenishment layer includes a lithium replenishment material. In some embodiments of this application, the positive electrode material layer includes an active material, a conductive agent, and a binder, and the lithium replenishment layer includes a lithium replenishment material, a conductive agent, and a binder. In some embodiments, the preparation method of the positive electrode sheet includes a coating method, which includes: mixing the positive electrode material, the conductive agent, the binder, and a solvent to form a positive electrode slurry; coating the positive electrode slurry onto the surface of the current collector to form a positive electrode material layer; and then applying the lithium replenishment material, the conductive agent, and the binder onto the surface of the positive electrode material layer to form a lithium replenishment layer, thereby obtaining the positive electrode sheet.

[0046] This application also provides a secondary battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode includes the positive electrode sheet as provided in this application. Please refer to... Figure 1 , Figure 1This is a schematic diagram of the structure of a secondary battery provided in one embodiment of this application. The secondary battery includes a positive electrode 10, a negative electrode 20, a separator 30, and an electrolyte 40. During charging, lithium ions are released from the positive electrode 10, pass through the electrolyte 40, and are deposited on the negative electrode 20; during discharging, lithium ions are released from the negative electrode 20, pass through the electrolyte 40, and are embedded in the positive electrode 10. The secondary battery provided in this application has high capacity and cycle performance due to the use of the positive electrode sheet of this application. In the embodiments of this application, the secondary battery includes a lithium secondary battery.

[0047] In some embodiments of this application, the negative electrode of the secondary battery includes one or more of carbon-based negative electrodes and lithium negative electrodes. The carbon-based negative electrode may include one or more of graphite, hard carbon, soft carbon, and graphene; the lithium negative electrode may include metallic lithium or lithium alloys, specifically lithium-silicon alloys, lithium-sodium alloys, lithium-potassium alloys, lithium-aluminum alloys, lithium-tin alloys, and lithium-indium alloys. In some embodiments of this application, the current collector of the negative electrode includes copper foil; the negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, and soft carbon; the binder includes one or more of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), and styrene-butadiene latex (SBR); and the conductive agent includes one or more of acetylene black, Ketjen carbon black, Super-P, carbon nanotubes, carbon nanofibers, activated carbon, and graphene. In this application, the negative electrode can be prepared using any method known in the art.

[0048] In this application, the separator of the secondary battery can be any separator known to those skilled in the art. For example, the separator can be one or more of polyolefin microporous membrane, polyethylene terephthalate, polyethylene felt, glass fiber felt or ultrafine glass fiber paper.

[0049] In this application, the electrolyte of the secondary battery comprises a solution of an electrolyte lithium salt in a non-aqueous solvent. In embodiments of this application, the electrolyte lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorosilicate (Li2SiF6), lithium tetraphenylborate (LiB(C6H5)4), lithium chloride (LiCl), lithium bromide (LiBr), lithium chloroaluminate (LiAlCl4), lithium fluorocarbon sulfonate (LiC(SO2CF3)3), LiCH3SO3, LiN(SO2CF3)2, and LiN(SO2C2F5)2. In some embodiments of this application, the non-aqueous solvent includes one or more of chain esters and cyclic esters. In some embodiments of this application, the chain ester includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), methyl propyl carbonate (MPC), and dipropyl carbonate (DPC). In some embodiments of this application, the chain esters include fluorinated, sulfur-containing, or unsaturated chain organic esters. In some embodiments of this application, the cyclic esters include one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), γ-butyrolactone (γ-BL), and sulpholactone. In some embodiments of this application, the cyclic esters include fluorinated, sulfur-containing, or unsaturated cyclic organic esters. In some embodiments of this application, the non-aqueous solvent includes one or more of chain ethers and cyclic ether solutions. In some embodiments of this application, the cyclic ethers include one or more of tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,3-dioxolane (DOL), and 4-methyl-1,3-dioxolane (4-MeDOL).

[0050] In some embodiments of this application, the cyclic ethers include fluorine-containing, sulfur-containing, or unsaturated cyclic organic ethers. In some embodiments of this application, the chain ethers include one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), 1,2-dimethoxypropane (DMP), and diethylene glycol dimethyl ether (DG).

[0051] In some embodiments of this application, the chain ether includes fluorine-containing, sulfur-containing, or unsaturated chain organic ethers. In some embodiments of this application, the concentration of the electrolyte lithium salt in the electrolyte is 0.1 mol / L-15 mol / L. In some embodiments of this application, the concentration of the electrolyte lithium salt is 1 mol / L-10 mol / L.

[0052] In the embodiments of this application, the battery can be fabricated using either a lamination process or a winding process. In some embodiments of this application, the battery is fabricated using a lamination process.

[0053] This application also provides an electronic device that includes a secondary battery provided in this application, which powers the electronic device.

[0054] The technical solution of this application will be further described below with reference to several embodiments.

[0055] Example 1

[0056] A lithium supplement material, the preparation method of which includes:

[0057] Oxalic acid and sulfurous acid were mixed in a molar ratio of 9:1 to obtain a mixed solution. Lithium hydroxide was added to the mixed solution to obtain a mixed solution of lithium oxalate and lithium sulfite. The mixed solution was then evaporated and crystallized at 60°C to obtain Li2(C2O4). 0.9 (SO3) 0.1 ·zH2O, which will react with Li2(C2O4) 0.9 (SO3) 0.1 ·zH2O was dried under vacuum at 150℃ to obtain anhydrous Li2(C2O4). 0.9 (SO3) 0.1 For Li2(C2O4) 0.9 (SO3) 0.1 The material was ground to obtain a lithium supplement material with an average particle size of 0.3 μm.

[0058] To test the decomposition voltage of the obtained lithium-added material, a test battery was prepared using the lithium-added material as the positive electrode material. The preparation method of the test battery is as follows:

[0059] Acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersant. The positive electrode slurry was prepared by uniformly mixing the lithium-containing material with acetylene black in a mass ratio of 85:10:5:50. Aluminum foil was used as the current collector for coating, and the slurry was then vacuum-dried in a 120℃ oven for 24 hours. After pressing and rolling, the positive electrode sheet was formed. A lithium metal sheet was used as the negative electrode, a polypropylene porous membrane as the separator, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) as the electrolyte. The test battery was assembled in an argon-filled glove box to obtain test battery sample C1.

[0060] Example 2

[0061] A lithium supplement material, the preparation method of which includes:

[0062] Oxalic acid and sulfurous acid were mixed in a molar ratio of 92:8 to obtain a mixed solution. Lithium hydroxide was added to the mixed solution to obtain a mixed solution of lithium oxalate and lithium sulfite. The mixed solution was then evaporated and crystallized at 60°C to obtain Li2(C2O4). 0.92(SO3) 0.08 ·zH2O, which will react with Li2(C2O4) 0.92 (SO3) 0.08 ·zH2O was dried under vacuum at 150℃ to obtain anhydrous Li2(C2O4). 0.92 (SO3) 0.08 For Li2(C2O4) 0.92 (SO3) 0.08 The material was ground to obtain a lithium supplement material with an average particle size of 0.3 μm.

[0063] To test the decomposition voltage of the obtained lithium-added material, a test battery was prepared using the lithium-added material as the positive electrode material. The preparation method of the test battery is as follows:

[0064] Acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersant. The positive electrode slurry was prepared by uniformly mixing the lithium-containing material with acetylene black in a mass ratio of 85:10:5:50. Aluminum foil was used as the current collector for coating, and the slurry was then vacuum-dried in a 120℃ oven for 24 hours. After pressing and rolling, the positive electrode sheet was formed. A lithium metal sheet was used as the negative electrode, a polypropylene porous membrane as the separator, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) as the electrolyte. The test battery was assembled in an argon-filled glove box, resulting in test battery sample C2.

[0065] Example 3

[0066] A lithium supplement material, the preparation method of which includes:

[0067] Oxalic acid and sulfurous acid were mixed in a molar ratio of 96:4 to obtain a mixed solution. Lithium hydroxide was added to the mixed solution to obtain a mixed solution of lithium oxalate and lithium sulfite. The mixed solution was then evaporated and crystallized at 60°C to obtain Li2(C2O4). 0.96 (SO3) 0.04 ·zH2O, which will react with Li2(C2O4) 0.96 (SO3) 0.04 ·zH2O was dried under vacuum at 150℃ to obtain anhydrous Li2(C2O4). 0.96 (SO3) 0.04 For Li2(C2O4) 0.96 (SO3) 0.04 The material was ground to obtain a lithium supplement material with an average particle size of 0.3 μm.

[0068] To test the decomposition voltage of the obtained lithium-added material, a test battery was prepared using the lithium-added material as the positive electrode material. The preparation method of the test battery is as follows:

[0069] Acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersant. The positive electrode slurry was prepared by uniformly mixing the lithium-containing material with acetylene black in a mass ratio of 85:10:5:50. Aluminum foil was used as the current collector for coating, and the slurry was then vacuum-dried in a 120℃ oven for 24 hours. After pressing and rolling, the positive electrode sheet was formed. A lithium metal sheet was used as the negative electrode, a polypropylene porous membrane as the separator, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) as the electrolyte. The test battery was assembled in an argon-filled glove box, resulting in test battery sample C3.

[0070] Example 4

[0071] A lithium supplement material, the preparation method of which includes:

[0072] Oxalic acid and sulfurous acid were mixed in a molar ratio of 4:1 to obtain a mixed solution. Lithium hydroxide was added to the mixed solution to obtain a mixed solution of lithium oxalate and lithium sulfite. The mixed solution was then evaporated and crystallized at 60°C to obtain Li2(C2O4). 0.8 (SO3) 0.2 ·zH2O, which will react with Li2(C2O4) 0.8 (SO3) 0.2 ·zH2O was dried under vacuum at 150℃ to obtain anhydrous Li2(C2O4). 0.8 (SO3) 0.2 For Li2(C2O4) 0.8 (SO3) 0.2 The material was ground to obtain a lithium supplement material with an average particle size of 0.3 μm.

[0073] To test the decomposition voltage of the obtained lithium-added material, a test battery was prepared using the lithium-added material as the positive electrode material. The preparation method of the test battery is as follows:

[0074] Acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersant. The positive electrode slurry was prepared by uniformly mixing the lithium-containing material with acetylene black in a mass ratio of 85:10:5:50. Aluminum foil was used as the current collector for coating, and the slurry was then vacuum-dried in a 120℃ oven for 24 hours. After pressing and rolling, the positive electrode sheet was formed. A lithium metal sheet was used as the negative electrode, a polypropylene porous membrane as the separator, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) as the electrolyte. The test battery was assembled in an argon-filled glove box to obtain test battery sample C4.

[0075] Example 5

[0076] The composition of the lithium replenishing material in Example 5 was the same as that in Example 1, except that the average particle size of the lithium replenishing material in Example 5 was 500 μm. The test battery C5 was prepared using the same method as in Example 1.

[0077] Example 6

[0078] The composition of the lithium replenishing material in Example 6 is the same as that in Example 1, except that the average particle size of the lithium replenishing material in Example 6 is 15 μm. The test battery C6 was prepared using the same method as in Example 1.

[0079] Example 7

[0080] In Example 7, the composition and particle size of the lithium replenishing material were the same as in Example 1, that is, the lithium replenishing material was Li2(C2O4) with an average particle size of 0.3 μm. 0.9 (SO3) 0.1 .

[0081] To test the lithium replenishment effect of the lithium replenishment material in the battery, a secondary battery was prepared by combining the lithium replenishment material with the positive electrode material. The preparation method of the secondary battery is as follows:

[0082] Lithium iron phosphate (LiFePO4) was used as the positive electrode material. The active material was obtained by mixing lithium iron phosphate and lithium supplementation material at a mass ratio of 96.4:3.6. Acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) was used as a binder, and N-methylpyrrolidone (NMP) was used as a dispersant. The active material:acetylene black:PVDF:NMP was mixed evenly at a mass ratio of 85:10:5:50 to obtain the positive electrode slurry. Aluminum foil was used as the current collector for coating. Then, it was placed in a 120℃ oven for vacuum drying for 24 hours. After pressing and rolling, it was made into a positive electrode sheet.

[0083] Graphite, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 100:3:2 and coated onto copper foil. After drying, the mixture is rolled and slit to obtain the negative electrode sheet.

[0084] Using a polypropylene porous membrane as the separator, and a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) in 1 mol / L LiPF6 (volume ratio = 1:1) as the electrolyte, the secondary battery was assembled in an argon-filled glove box to obtain secondary battery sample S1.

[0085] Example 8

[0086] In Example 8, the composition and particle size of the lithium replenishing material were the same as in Example 2, that is, the lithium replenishing material was Li2(C2O4) with an average particle size of 0.3 μm. 0.92 (SO3) 0.08 .

[0087] Secondary battery sample S2 was prepared using the same method as in Example 7.

[0088] Example 9

[0089] In Example 9, the composition and particle size of the lithium replenishing material are the same as in Example 3, that is, the lithium replenishing material is Li2(C2O4) with an average particle size of 0.3 μm. 0.96 (SO3) 0.04 .

[0090] Secondary battery sample S3 was prepared using the same method as in Example 7.

[0091] Example 10

[0092] In Example 10, the composition and particle size of the lithium replenishing material were the same as in Example 4, that is, the lithium replenishing material was Li2(C2O4) with an average particle size of 0.3 μm. 0.8 (SO3) 0.2 .

[0093] Secondary battery sample S4 was prepared using the same method as in Example 7.

[0094] Example 11

[0095] The composition and particle size of the lithium replenishing material in Example 11 are the same as those in Example 5, that is, the lithium replenishing material is Li2(C2O4) with an average particle size of 500 μm. 0.9 (SO3) 0.1 .

[0096] Secondary battery sample S5 was prepared using the same method as in Example 7.

[0097] Example 12

[0098] The composition and particle size of the lithium replenishing material in Example 12 are the same as those in Example 6, that is, the lithium replenishing material is Li2(C2O4) with an average particle size of 15 μm. 0.9 (SO3) 0.1 .

[0099] Secondary battery sample S6 was prepared using the same method as in Example 7.

[0100] Example 13

[0101] In Example 13, the composition and particle size of the lithium replenishing material were the same as in Example 7, that is, the lithium replenishing material was Li2(C2O4) with an average particle size of 0.3 μm. 0.9 (SO3) 0.1The difference from Example 7 is that in Example 13, lithium iron phosphate and lithium replenishment material were mixed at a mass ratio of 90:10 to obtain active material, and secondary battery sample S7 was prepared using the same method as in Example 7.

[0102] Example 14

[0103] In Example 14, the composition and particle size of the lithium replenishing material were the same as in Example 7, that is, the lithium replenishing material was Li2(C2O4) with an average particle size of 0.3 μm. 0.9 (SO3) 0.1 The difference from Example 7 is that in Example 14, lithium iron phosphate and lithium replenishment material were mixed at a mass ratio of 99:1 to obtain active material, and secondary battery sample S8 was prepared using the same method as in Example 7.

[0104] Example 15

[0105] In Example 15, the composition and particle size of the lithium replenishing material were the same as in Example 7, that is, the lithium replenishing material was Li2(C2O4) with an average particle size of 0.3 μm. 0.9 (SO3) 0.1 The difference from Example 7 is that the preparation method of the secondary battery in Example 15 is as follows:

[0106] Lithium iron phosphate (LiFePO4) was used as the positive electrode material. A positive electrode slurry was prepared by uniformly mixing the positive electrode material, acetylene black, PVDF, and NMP in a mass ratio of 100:2:3:40. The slurry was coated with aluminum foil as the current collector and dried to obtain the positive electrode material layer. A lithium supplement slurry was prepared by uniformly mixing the lithium supplement material, acetylene black, PVDF, and NMP in a mass ratio of 5:2:3:40. The lithium supplement slurry was coated on the surface of the positive electrode material layer and then vacuum dried in an oven at 120°C for 24 hours. After pressing and rolling, the positive electrode sheet was formed.

[0107] Graphite, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 100:3:2 and coated onto copper foil. After drying, the mixture is rolled and slit to obtain the negative electrode sheet.

[0108] Using a polypropylene porous membrane as the separator, and a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) in 1 mol / L LiPF6 (volume ratio = 1:1) as the electrolyte, the secondary battery was assembled in an argon-filled glove box to obtain secondary battery sample S9.

[0109] To highlight the beneficial effects of this application, the following comparative examples are provided.

[0110] Comparative Example 1

[0111] In Comparative Example 1, the lithium supplement material was lithium oxalate, namely Li2C2O4, with an average particle size of 0.3 μm.

[0112] The lithium replenishment material was prepared into a test battery using the same method as in Example 1. The test battery was designated DC1.

[0113] The secondary battery sample DS1 was prepared by using the same method as in Example 7 to combine the lithium replenishment material and the cathode material.

[0114] Comparative Example 2

[0115] In Comparative Example 2, the lithium supplement material was lithium oxalate with an average particle size of 500 μm, namely Li2C2O4.

[0116] The lithium-supplementing material was prepared into a test battery using the same method as in Example 1. The test battery was designated DC2.

[0117] The secondary battery sample DS2 was prepared by using the same method as in Example 7 to combine the lithium replenishment material and the cathode material.

[0118] Comparative Example 3

[0119] The secondary battery of Comparative Example 3 did not add lithium replenishment material. Its positive electrode sheet used lithium iron phosphate (LiFePO4) as the positive electrode material. Lithium iron phosphate, acetylene black, PVDF and NMP were mixed evenly in a mass ratio of 85:10:5:50 to obtain a positive electrode slurry. After preparing the positive electrode sheet, the secondary battery sample DS3 was prepared by the same method as in Example 7.

[0120] Effect Example

[0121] To strongly support the beneficial effects of the technical solutions in the embodiments of this application, the following tests are provided:

[0122] 1) Using a carbon-sulfur elemental analyzer, the lithium replenishment materials of Examples 1-4 were subjected to elemental quantitative analysis to obtain the molar ratio of carbon atoms to sulfur atoms in the lithium replenishment materials (carbon-sulfur ratio). The test results are shown in Table 1.

[0123] Table 1. Carbon-sulfur ratio of lithium-supplementing materials in Examples 1-4

[0124] Example 1 18.21 Example 2 23.54 Example 3 47.69 Example 4 8.43

[0125] 2) The decomposition performance of the lithium replenishment materials in Examples 1-6 and Comparative Examples 1-2 was tested. The decomposition performance of the lithium replenishment materials includes two aspects: one is the capacity of active lithium that can be released after delithiation, i.e., the initial delithiation specific capacity; the other is the decomposition delithiation potential, i.e., the initial charging voltage plateau. The lower the decomposition plateau voltage and the higher the delithiation specific capacity, the better the lithium replenishment performance of the lithium replenishment material.

[0126] Test batteries from Examples 1-6 and Comparative Examples 1-2 were used to perform charge-discharge specific capacity tests on a charge-discharge tester. The decomposition and delithiation potential of the lithium replenishment material and the initial delithiation specific capacity were tested. Specifically, the battery was set to a charging state (i.e., working electrode delithiation) with a charging current density of 0.1C. Charging was stopped when the cutoff voltage reached 4.6V or 4.8V, and the initial charge specific capacity was calculated. After the initial delithiation, the battery was set to a discharging state (i.e., working electrode lithium insertion) with a discharging current density of 0.1C. Discharging was stopped when the cutoff voltage reached 3V, and the initial discharge specific capacity was calculated. Wherein, the initial discharge specific capacity (mAh / g) = initial discharge capacity / mass of active material; the theoretical initial delithiation specific capacity (mAh / g) = theoretical Li total delithiation capacity / mass of active material; the initial delithiation specific capacity (mAh / g) = initial delithiation capacity / mass of active material.

[0127] Please see Figures 2-4 ,in, Figure 2 The charge-discharge curves of the test batteries in Examples 1-3 are shown. Figure 3 The charge-discharge curves of the test batteries in Examples 4-6 are shown. Figure 4 The charge-discharge curves of the test batteries for comparative examples 1-2 are shown. Figures 2-4 In the figure, the horizontal axis Capacity represents the battery capacity in mAh, and the vertical axis Voltage represents the potential in V. During the first charge, the lithium replenishment material begins to decompose and release active lithium at a certain voltage plateau. The decomposition voltage and the initial delithiation specific capacity of the lithium replenishment material are recorded. Please refer to Table 2 for the test results.

[0128] Table 2. Decomposition performance of lithium-supplementing materials from Examples 1-6 and Comparative Examples 1-2

[0129]

[0130] Depend on Figures 2-4 As can be seen from Table 2, the decomposition voltage of the lithium replenishment materials in Comparative Example 1 and Comparative Example 2 is greater than or equal to 4.8V, while the lithium replenishment material of this application, due to the addition of SO3 dopant ions... 2- Therefore, it has a low delithiation potential, and with the addition of SO3 dopant ions... 2- As the content increases, the decomposition potential of the lithium replenishment material also decreases. When the lithium replenishment material is applied to the secondary battery, the lithium replenishment material can fully release active lithium during the first charge of the secondary battery, thereby increasing the actual usable active lithium content. In addition, as can be seen from Table 2, the particle size of the lithium replenishment material also affects the decomposition voltage. The lithium replenishment material with a smaller particle size has a lower decomposition voltage than the lithium replenishment material with a larger particle size.

[0131] 3) The decomposition performance of the lithium replenishment material was tested on the secondary battery samples of Examples 7-15 and Comparative Examples 1-2. The purpose was to study the decomposition performance of the lithium replenishment material in the secondary battery. The same method as in (2) was used to test the secondary battery samples of Examples 7-15 and Comparative Examples 1-2. The Li content in the lithium replenishment material was obtained by comparing the charging voltage plateau. + The exit plateau potential was determined, and the test results are shown in Table 3.

[0132] Table 3. Decomposition performance of lithium-replenishing materials in secondary batteries in Examples 7-15 and Comparative Examples 1-2.

[0133]

[0134] As shown in Table 3, in the lithium iron phosphate battery system, the delithiation plateau potential of the lithium replenishment materials in Comparative Examples 1 and 2 is greater than 4.8V. Under this voltage condition, lithium iron phosphate is prone to irreversible structural changes, thereby reducing the battery cycle performance. In contrast, the lithium replenishment material of this application has a lower delithiation potential, which is beneficial for protecting the cathode material and extending the battery's lifespan.

[0135] 4) Battery performance tests were conducted on the secondary battery samples of Examples 7-15 and Comparative Examples 1-3 to verify the lithium replenishment effect of the lithium replenishment material. The charge and discharge regime during the test was as follows: the charging cutoff voltage was 4.85V and the discharge cutoff voltage was 2.00V. The first charge capacity and the first discharge capacity of each secondary battery sample were recorded, and the first cycle efficiency of the secondary battery was obtained. The test results are shown in Table 4.

[0136] Table 4 Performance of Secondary Batteries in Examples 7-15 and Comparative Examples 1-2

[0137]

[0138] As shown in Table 4, the secondary battery in Comparative Example 3, without the addition of lithium replenishment material, had an initial charge capacity of 1087.2 mAh for its positive electrode material, LiFePO4. The formation of the SEI film on the negative electrode consumed approximately 11.25% of the active lithium, resulting in only 964.9 mAh being re-intercalated during the first discharge. In contrast, the lithium replenishment materials added in other experiments could decompose during charging to provide active lithium, thus improving the initial efficiency. However, the lithium replenishment materials in Comparative Examples 1 and 2, due to their high decomposition voltage, could not decompose sufficiently within the charging voltage range, resulting in limited lithium replenishment and poor battery cycle performance. Furthermore, the SO3 lithium replenishment material in Example 4... 2- The content is relatively high. Since lithium sulfate has low solubility in organic solvents, the sulfate ions generated in the reaction may form a new crystal phase structure on the cathode material together with lithium ions, which will affect the battery performance.

[0139] The above description represents the preferred embodiments of this application, but should not be construed as limiting the scope of this application. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this application, and these improvements and modifications are also considered to be within the scope of protection of this application.

Claims

1. A lithium supplementation material, characterized in that, Including those with the chemical formula Li2(C2O4) x (SO3) y Compounds in which x + y = 1, 0.9 ≤ x < 1 and 0.001 ≤ y ≤ 0.

1.

2. The lithium replenishment material as described in claim 1, characterized in that, The ratio of x to y is greater than or equal to 9.

3. The lithium replenishment material as described in claim 1 or 2, characterized in that, The average particle size of the lithium replenishment material is 1 nm to 20 μm.

4. The lithium replenishment material as described in claim 1 or 2, characterized in that, The decomposition potential of the lithium replenishment material is less than or equal to 4.6V.

5. A positive electrode sheet, characterized in that, The positive electrode includes an active material and a lithium supplementation material as described in any one of claims 1-4.

6. The positive electrode sheet as described in claim 5, characterized in that, The positive electrode includes a current collector and an active material layer disposed on the current collector, wherein the active material layer includes the active material and the lithium supplementation material; Alternatively, the positive electrode may include a current collector, a positive electrode material layer, and a lithium replenishment layer arranged sequentially, wherein the positive electrode material layer includes the active material, and the lithium replenishment layer includes the lithium replenishment material.

7. The positive electrode sheet as described in claim 5, characterized in that, The mass ratio of the lithium replenishing material to the active material is 1:(5~1000).

8. The positive electrode sheet according to any one of claims 5-7, characterized in that, The active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxide phosphate, lithium vanadium oxide, and lithium-rich manganese-based materials.

9. A secondary battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode includes a positive electrode sheet as described in any one of claims 5-8.

10. An electronic device, characterized in that, The electronic device includes the secondary battery as described in claim 9.

Citation Information

Patent Citations

  • Modified lithium oxalate as well as preparation method and application thereof

    CN114300680A